Cataract surgery-related anxiety and stress among nurses working in the operating theatre - AlMarhoon, Mashael; Ahmad, Khabir; Mousa, Ahmed; Bin Helayel, Halah (KHD-Production, 2025)
Operating room nurses (ORNs) can be negatively affected when they experience unpleasant personalities and attitudes from ophthalmic surgeons, which can adversely impact their work performance, cognitive skills, and psychological health. This study aims to assess anxiety and stress levels and identify factors associated with negative emotions among OR nurses, especially during intraoperative adverse events in cataract surgery. A self-administered questionnaire was designed and distributed among 36 operating room nurses at a tertiary eye hospital in Riyadh, Saudi Arabia, from August to October 2023. The questionnaire aimed to assess anxiety levels and explore the reasons for stress and anxiety associated with either complicated or uncomplicated phacoemulsification cases. Our research identified that two-thirds (66.7%) of participants experienced anxiety during cataract surgery. Moreover, the results showed that anxious feelings during uncomplicated cataract surgery were reported by 26 (72.2%) nurses when working with a consultant with an unpleasant personality and 14 (38.9%) nurses when the patient was uncooperative. Two-thirds of the respondents (66.7%) were anxious when they experienced a negative attitude from the consultant, and more than half of the nurses (63.9%) were nervous due to the unavailability of sterile instruments during complicated cataract surgery. Furthermore, (41.7%) of nurses reported losing concentration when a surgeon displayed a negative attitude. Unfavorable attitudes and behaviors by ophthalmic consultants and surgeons may be the most prevalent factors in encountering anxiety and discomfort among OR nurses.